Coupled Error Dynamic Formulation for Modal Control of a Two Link Manipulator Having Two Revolute Joints (Global Journals of Research in Engineering, 2022)
In the present work reformulation of the dynamics of a planar two-link manipulator has been presented in the form of joint errors and their derivatives The linear second-order differential equations with time-varying coefficients represent the Coupled Error Dynamics of the system In these equations the non-linear centrifugal and Coriolis terms are expressed as linear functions of joint error rates and the non-linear gravity terms as a linear function of joint errors with time-varying coefficients After inclusion of linearized version of these terms the concept of modal analysis is used in the design of a control system for the robot The developed control approach is compared with the commonly used computed-torque control approach as applied for a high-speed direct-drive two-link manipulator with revolute joints Thus in the proposed approach for controller design the system non-linearities are taken as part of the system representation itself instead of disturbances as assumed in existing approaches
Keywords: coupled error dynamics; computed-torque control; modal analysis; rigid robot; IMSC